Where methadone is now in NY: Take‐home flexibility, OTP concerns. Issue 24 (18th June 2022) - Knopf, Alison
Abstract : A symposium sponsored last week by the Coalition of Medication Assisted Treatment Providers and Advocates (COMPA) focused on treatment for opioid use disorder (OUD) with methadone, which is only done in opioid treatment programs (OTPs). Officials from the Office of Addiction Services and Supports (OASAS) — the New York agency that is responsible for regulation and oversight of OTPs and distribution of the federal Substance Abuse Prevention and Treatment (SAPT) Block Grant — presented an update of COVID and post‐COVID rules.